Virtual environments of teaching and learning. Content to systematize the process of professional development of teachers - Felipe Manuel León-Cáceres; José Raúl Moracén-Cuevas; Ana Norvis Caballero-Rodríguez (Santiago, 2016)
The virtual teaching-learning are an expression of the use of information technology and communication in the educational field, since they have become for education a necessity and imperative to contextualize them in line with scientific and technical development. It is therefore of great importance for science teaching, promote professional development for teachers in the use of virtual environments, so that they assume responsibility perform their profession, for future graduates require to use them in their jobs and they have become an inexhaustible source of knowledge and know-how. Why this paper aims to provide some pedagogical reflections on the teaching model of systematization of the professional development of teachers to use virtual environments as a result of a doctoral thesis.